2004
DOI: 10.1196/annals.1309.058
|View full text |Cite
|
Sign up to set email alerts
|

Orally and Nasally Induced Tolerance Studies in Ocular Inflammatory Disease: Guidance for Future Interventions

Abstract: The induction of both oral and nasal tolerance has been used in both experimental models of ocular disease and clinically. Initial work centered around the abrogation of experimental autoimmune uveitis using either one or two whole uveitogenic antigens. Other models of ocular disease have included a corneal transplant model, demonstrating that feeding splenocytes from the donor strain of rats enhanced corneal engraftment. Fragments of pertinent antigens have been shown to alter the expression of experimental u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Abrogation of experimental autoimmune uveitis in animal models was effective using either one or two whole uveitogenic antigens [135]. A randomized study in uveitis demonstrated that single antigen feeding provided far better protection than feeding of multiple antigens [135].…”
Section: Should We Change the Target Antigen?mentioning
confidence: 98%
See 1 more Smart Citation
“…Abrogation of experimental autoimmune uveitis in animal models was effective using either one or two whole uveitogenic antigens [135]. A randomized study in uveitis demonstrated that single antigen feeding provided far better protection than feeding of multiple antigens [135].…”
Section: Should We Change the Target Antigen?mentioning
confidence: 98%
“…A randomized study in uveitis demonstrated that single antigen feeding provided far better protection than feeding of multiple antigens [135]. On the other hand, the use of oral anti-CD3 antibodies led to suppression of antigen-specific immune responses to administration of non-antigen-specific peptides [102,118 -120].…”
Section: Should We Change the Target Antigen?mentioning
confidence: 99%
“…One such strategy is vaccination against antigen driven immune responses. 82 Another approach would be the use of oral and nasal tolerance using antigens which stimulate the adoptive immune response, which has been shown to have an effect on uveitis and other disorders 83,84 and recently has been shown to have an effect on atherosclerosis. 85 Therapy could begin once large drusen and pigmentary changes are noted, since this is the hallmark of increased risk of advanced AMD.…”
Section: What Are the Implications For Therapy?mentioning
confidence: 99%